2021
DOI: 10.3390/proteomes9010013
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Landscape of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most prevalent form of dementia, and the numbers of AD patients are expected to increase as human life expectancy improves. Deposition of β-amyloid protein (Aβ) in the extracellular matrix and intracellular neurofibrillary tangles are molecular hallmarks of the disease. Since the precise pathophysiology of AD has not been elucidated yet, effective treatment is not available. Thus, understanding the disease pathology, as well as identification and development of valid biomarkers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 130 publications
(149 reference statements)
0
11
0
Order By: Relevance
“…The results obtained in this explorative AP-MS study represent a starting point for next proteomic investigations, supported by technical verification with immunological techniques, to be performed on a larger cohort of patients at different stages of the disease progression and on other neurodegenerative diseases. It has been repeatedly stressed by various research groups that understanding the events responsible for AD pathogenesis requires the use of different proteomic strategies [ 17 , 18 , 20 , 42 ]; as suggested by Jain AP et al the understanding of molecular mechanisms and cellular signaling pathways involved in AD pathogenesis is needed for discovering new targets and developing new therapeutic strategies [ 20 ], as well as for the diagnostic and disease progression monitoring. To date, several proteomic studies have identified candidate biomarkers of AD in brain tissue and CSF [ 17 , 18 , 20 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results obtained in this explorative AP-MS study represent a starting point for next proteomic investigations, supported by technical verification with immunological techniques, to be performed on a larger cohort of patients at different stages of the disease progression and on other neurodegenerative diseases. It has been repeatedly stressed by various research groups that understanding the events responsible for AD pathogenesis requires the use of different proteomic strategies [ 17 , 18 , 20 , 42 ]; as suggested by Jain AP et al the understanding of molecular mechanisms and cellular signaling pathways involved in AD pathogenesis is needed for discovering new targets and developing new therapeutic strategies [ 20 ], as well as for the diagnostic and disease progression monitoring. To date, several proteomic studies have identified candidate biomarkers of AD in brain tissue and CSF [ 17 , 18 , 20 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these diagnostic tools are limited by their costs (PET- and brain-MRI), and complexity, or invasiveness (CSF study). Many peripheral diagnostic biomarkers have been proposed, but still none have shown to be sensitive and specific enough to be considered good candidates [ 18 , 19 , 20 ]. Therefore, it is a global challenge to find novel, peripheral potential biomarkers useful for developing effective screening methods for large-scale application.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical proteomics have been used for almost three decades to discover diagnostic markers in neurodegenerative disorders (see [11][12][13][14][15][16][17][18][19][20]). These studies concentrated on AD and have used brain tissue, cerebrospinal fluid and blood as substrates for analysis.…”
Section: Introductionmentioning
confidence: 99%